Efektivitas Penggunaan Catok Crimper dan Hair Powder terhadap Sasakan Sanggul pada Mata Kuliah Pengantin Jawa - Ratna Nur Yunida; Ifa Nurhayati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Javanese bridal bun styling requires the right backcombing technique to produce a dense, neat bun shape, and has good durability. However, problematic hair characteristics such as thin, slippery, and oily hair often become obstacles in the process of forming a backcombing. This study aims to analyze the effectiveness of using a crimper and hair powder on the quality of the backcombing bun in the Javanese Bridal course. This study used a quasi-experimental method with a one-group pretest-posttest design with two treatments (split treatment design). The research sample taken was 12 students of the Beauty Education Study Program selected using a purposive sampling technique. Data collection was carried out through sensory testing using a questionnaire with a dichotomous scale (Yes/No). Data analysis was carried out descriptively, as well as through prerequisite tests including the normality test (Shapiro-Wilk) and the homogeneity test (Levene). Furthermore, hypothesis testing was carried out using paired sample t-test and independent sample t-test with the help of the SPSS program at a significance level of 5%. Based on the research results, the use of a crimping iron and hair powder were both proven to be equally effective in significantly improving the quality of the hair bun (p < 0.05). However, the results of the independent sample t-test showed no significant difference in effectiveness between the two methods (p = 0.107 > 0.05). Both techniques can be considered to have equal levels of effectiveness in improving the quality of the hair bun. Therefore, the use of a crimping iron and hair powder can be used as alternative techniques to improve the quality of the hair bun during the learning process of Javanese bridal hair styling.